Origins and meanings of the Russian Socialism - Konstantin Kondratiev, Tatiana Shatunova, (Opción, 2019)
The article discusses the causes of socialism collapse in Russia, related to the social history of the Russian proletariat. The study applied the socio-philosophical approach and the method of specific historical analysis. As the result, they showed that the social content of socialism demise process in Russia is paradoxically related to the total process of population proletarianization. In conclusion, two versions of the proletarianization process were created in the history of the socialist development of Russia. The explication of this phenomenon is significant to understand current social processes not only in Russia, but also in the modern world.